Survey of the status of copper, interacting minerals, and vitamin E levels in the livers of sheep in Ontario - Menzies, Paula I. (2003)
Livers from cull ewes and market lambs raised in Ontario were obtained to determine the status of specific minerals and vitamin E. Values for copper (Cu), iron (Fe), manganese (Mn), and zinc (Zn) obtained by atomic absorption and inductively coupled plasma — atomic emission spectroscopy (ICP-AES) were found to be statistically different but sufficiently biologically similar to allow the use of ICP-AES for screening groups of samples for deficient or toxic levels of those minerals. Toxic levels of cadmium were not found. Toxic levels of aluminum were found in 1 cull ewe and 1 market lamb. A significant proportion of both market lamb samples (40.0%) and cull ewe samples (50.0%) had high to toxic levels of Cu. In market lambs, Fe, Mn, molybdenum (Mo), selenium (Se), and Zn were not found to be important determinants of Cu level. In cull ewes, Fe, Mn, and Zn play a moderate role in the variability of liver Cu levels. Selenium was found to be present at marginal levels in 3.3% of cull ewe samples and in 42.6% of market lamb samples. Vitamin E was found to be low to deficient in 10.0% of cull ewe samples and in 90.0% of market lamb samples. In market lambs, only Mo was associated with Se levels, and no minerals were associated with vitamin E levels. In cull ewes, there was a strong association between Se and vitamin E. This survey demonstrates that marked nutritional imbalances of Cu, Se, and vitamin E exist in cull ewes and market lambs in Ontario.